CALTPP: A general program to calculate thermophysical properties. (1st April 2020) - Yuling, Liu; Cong, Zhang; Changfa, Du; Yong, Du; Zhoushun, Zheng; Shuhong, Liu; Lei, Huang; Shiyi, Wen; Youliang, Jin; Huaqing, Zhang; Fan, Zhang; George, Kaptay
Abstract: A program CALTPP (CALculation of ThermoPhysical Properties) is developed in order to provide various thermophysical properties such as diffusion coefficient, interfacial energy, thermal conductivity, viscosity and molar volume mainly as function of temperature and composition. These thermophysical properties are very important inputs for microstructure simulations and mechanical property predictions. The general structure of CALTPP is briefly described, and the CALPHAD-type models for the description of these thermophysical properties are presented. The CALTPP program contains the input module, calculation and/or optimization modules and output module. A few case studies including (a) the calculation of diffusion coefficient and optimization of atomic mobility, (b) the calculation of solid/liquid, coherent solid/solid and liquid/liquid interfacial energies, (c) the calculation of thermal conductivity, (d) the calculation of viscosity, and (e) the establishment of molar volume database in binary and ternary alloys are demonstrated to show the features of CALTPP. It is expected that CALTPP will be an effective contribution in both scientific research and education.